Analysis of costs and formation of the sale price of fruit and vegetables practiced by family farmers marketers in Cacoal - RO (Research, Society and Development, 2022)
The price formation process is more than a mathematical calculation, it is not just an attribution of value to the product, it tends to have variables to be analyzed, where this price dynamic can come together with tactics and strategies, in order to guarantee the organization's success. Given the above, the research on cost analysis and price formation practiced by family farmers marketers in Cacoal, aims to analyze the process of formation of sales price, costs, and their strategies. A descriptive research was carried out, with a qualitative, quantitative approach and a deductive method. The data collection techniques used were semi-structured interviews, non-participant observation, questionnaire and document research. The results point out that profitability is a key factor for staying in the fruit and vegetable production sector. Therefore, 58.06% do not use any type of financial or accounting control for price formation, followed by 41.67% use the cost plus the profit margin to determine the sales price, being linked to changes and variations due to the harvest, followed by competitors, among 55% of statements that at the beginning of the fair they analyze the prices of their competitors, and in the end they settle with lower prices using strategies and tactics, such as sales by volume and the quality of production, and among farmers, 57.97% sell and sell only in open markets in the municipality. Thus, studies on pricing tools in this commercial branch are suggested, seeking competitive advantage.